Analisis Determinan Kualitas Laba pada Perusahaan Manufaktur Sektor Indsutri Konsumsi - Devi Maya Sari (Program Studi Akuntansi Fakultas Ekonomi Universitas Samudra, 2025)
This study aims to analyze the effect of company size, company growth, and profitability on earnings quality in manufacturing companies in the consumer goods industry sector listed on the Indonesia Stock Exchange (IDX) for the period 2018–2024. The approach used is quantitative with an explanatory research type. The sample was determined using a purposive sampling technique and obtained 17 companies. Secondary data was obtained from annual financial reports through the official IDX website and analyzed using multiple linear regression with SPSS version 26. The results of the study indicate that partially, company size does not have a significant effect on earnings quality, while company growth and profitability have a significant effect. Simultaneously, all three variables have a significant effect on earnings quality, with profitability as the most dominant variable. These findings contribute to the development of literature and practical benefits for management, investors, and regulators. Further research is suggested to add variables such as leverage, ownership structure, or good corporate governance (GCG)